Electrochemical and/or microbiological treatment of pyrolysis wastewater. (October 2017) - Silva, José R.O.; Santos, Dara S.; Santos, Ubiratan R.; Eguiluz, Katlin I.B.; Salazar-Banda, Giancarlo R.; Schneider, Jaderson K.; Krause, Laiza C.; López, Jorge A.; Hernández-Macedo, Maria L.
Abstract: Electrochemical oxidation may be used as treatment to decompose partially or completely organic pollutants (wastewater) from industrial processes such as pyrolysis. Pyrolysis is a thermochemical process used to obtain bio-oil from biomasses, generating a liquid waste rich in organic compounds including aldehydes and phenols, which can be submitted to biological and electrochemical treatments in order to minimize its environmental impact. Thus, electrochemical systems employing dimensionally stable anodes (DSAs) have been proposed to enable biodegradation processes in subsurface environments. In order to investigate the organic compound degradation from residual coconut pyrolysis wastewater, ternary DSAs containing ruthenium, iridium and cerium synthetized by the 'ionic liquid method' at different calcination temperatures (500, 550, 600 and 700 °C) for the pretreatment of these compounds, were developed in order to allow posterior degradation by Pseudomonas sp., Bacillus sp. or Acinetobacter sp. bacteria. The electrode synthesized applying 500 °C displayed the highest voltammetric charge and was used in the pretreatment of pyrolysis effluent prior to microbial treatment. Regarding biological treatment, the Pseudomonas sp. exhibited high furfural degradation in wastewater samples electrochemically pretreated at 2.0 V. On the other hand, the use of Acinetobacter efficiently degraded phenolic compounds such as phenol, 4-methylphenol, 2, 5-methylphenol, 4-ethylphenol and 3, 5-methylphenol in both wastewater samples, with and without electrochemical pretreatment. Overall, the results indicate that the combination of both processes used in this study is relevant for the treatment of pyrolysis wastewater. Highlights: Pyrolysis wastewater was submitted to electrolytic and biological treatments. Acinetobacter sp. removed phenols from pure and pre-treated pyrolysis wastewater. Furfural degradation by electrochemical and biological treatments was observed.